HYBRID REED - SOLID-STATE DEVICES ARE A NEW GENERATION OF PROTECTIVE RELAYS - V. Gurevich (Elektrotehnìka ta Elektroenergetika, 2007)
Author’s approach allows viewing the problem of re-equipment of relay protection in a new way. In the author’s opinion combination of reed switches with magnetic circuits and semiconductor elements opens new avenues in development of the promising protective relays featuring reliability, simplicity and low cost. Examples of protective relays made with these elements are given below.